Tortured Logic: Information and brutality in interrogations (with debate) - Schiemann, John W. (Torture Journal, 2018)
Background: Pragmatic arguments for interrogational torture rest on the twin assumptions that torture generates reliable information and that torture can be controlled and limited. Click on pdf for full abstract.